Tanggung Jawab PT. KAI (Persero) Terhadap Kecelakaan Kereta Api Pada Keselamatan Penumpang - Andien Muarifah Primawati; Arief Suryono (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This article aims to examine the transportation of Indonesian Railways on passenger safety. Analyzing the Regulations related to the Railway Law for service users in the event of an accident on the Railway carrier. This research is a normative legal research. The author uses a statutory approach and a case approach. The legal sources used consist of primary legal materials and secondary legal materials. Legal material analysis techniques using (library research), namely with books, journals, articles, literature studies. The result of this research is that PT Kereta Api Indonesia is responsible to service users or passengers if they experience accidents due to operations on rail transportation with the closing of the party that bears the insurance, namely PT Jasa Raharja as the insurer to provide compensation to the insured party due to damage or loss and provide compensation to passengers who suffer losses, injuries, and deaths caused by the operation of this rail transportation transportation, the responsibility is carried out starting with passengers who are transported from the initial station to the next final station as evidenced by the agreement when the user is a passenger.